Effects of short-term heat stress on the activity of three antioxidant enzymes of predatory mite Neoseiulus barkeri (acari, phytoseiidae) - Li, Wei-Zhen; Zhu, Tong; Zhou, Jing-Jiang; Shang, Su-Qin (Frontiers in Physiology, 2022)
To study the physiological mechanisms of Neoseiulus barkeri in response to short-term heat stress, the eggs and the emerged adults were exposed to 38, 40, and 42°C, 85% ± 5%RH,16 h:8 h (L:D) for 2, 4, and 6 h. The activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) as well as the protein content of N. barkeri were examined. All treatments caused significant different changes compared to the untreated control. The protein content increased as the temperature increased, while it showed different changing trends with the prolongation of exposure duration. The enzymatic activity of SOD, CAT, and POD was significantly affected by the temperature treatment. Both the maximum and minimum level of the three enzymes after a short-term heat stress differed significantly to the control group (p < 0.05). The highest values of three enzymatic activities were all obtained at 40°C-4 h. Person correlation analysis indicates that the high temperature was the primary factor affecting the enzymatic activity, while the exposure duration of the heat stress was the secondary factor. In general, the short-term heat stress increased the protein content of Neoseiulus barkeri and up-regulated the expression of SOD, CAT, and POD activities as well.